The history of canine cruciate ligament surgery from 1952 – 2005 - Vaughan, L. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
This article is reprinted by kind permission of Veterinary History where it first appeared in Vol. 14, No. 2 (2008), pgs. 119–136. The paper is the text of an invited lecture that was given by the late Professor Leslie Vaughan. It has not been peer-reviewed, but is reprinted for readers of VCOT. An obituary to Professor Vaughan was published in VCOT 2009 22(3): IX-X.